SUSTAINABILITY OF STRATEGIC MANAGEMENT PRACTICE IN GOVERNMENT ORGANIZATION - Achmad Nurmandi, Cristhope Behren (LP3M UMY, 2012)
Since 1998, the Indonesian government had introduced an approach for Strategic Management under Government Regulation No. 108/2002. The government has not evaluated experiences with this strategy until now. However, in 2009, the administration of President Yudhoyono introduced a new approach entitled Rencana Pembangunan Jangka Menengah (RPJMD) –Medium Term Development Planning. Form and method of RPJM are quite different from the former management approach. In this paper, both writers investigate experiences with the attempt to introduce Strategic Management in Indonesian public sector, particularly the aspect of sustainability. Sustainability in this context means continuity of professional application of the method despite changes of political framework both at national and local level in a five-year period. The study found that sustainability of strategic planning according to the defined approach is linked to key aspects of professionalism: in terms of professional overall management (leadership), of professional coordination among governmental units, and of professional monitoring of the complete process and its instruments: planning, implementation and evaluation. On this basis, recommendations are given for a further professionalisation of Governance in Indonesia.